Intercultural Dialogue and Humanities from Late Antiquity to the Middle Ages - Di Palma, Enrico Maria (ETHICS IN PROGRESS, 2019)
The aim of this articole is to discover traces of humanitas in late antique and mediaval literature. Starting from the classic meaning of this notion, the paper finds three meaningful episodes: the controversy between Ambrosius and Symmachus about the Altar of Victory, the Dialogue of a Philosopher with a Jew and a Christian by Peter Abelard and the spread of the Life of Balaam and Josaphat. Through these examples, the article builds a new idea of humanitas, free from historical restricion, a blend of literary passion, acceptance of diversity and multiculturalism.